Bureaucratising Islam state strategies and Muslim responses in Singapore. Issue 3 (2nd September 2018) - Abdullah, Walid Jumblatt
ABSTRACT: Following transnational trends of Islamic resurgence, state-sponsored Islamic bureaucracies have occupied more prominence in Southeast Asia, particularly in the Malay Archipelago. The governments of Brunei, Indonesia, Malaysia, and Singapore have utilised 'administrative' religious bodies to fulfil certain objectives and, in the process, have impacted the discourse of Islam in their respective countries. Although the state-Muslim dynamics in these contexts differ widely, they share the objective of formalising classificatory schemes of Islam and outlining norms or rules for acceptable manifestations of Islam in the public domain. This paper investigates how the state in Singapore has drawn the boundaries for Islam's involvement in public affairs via this bureaucratisation. The attempt by the state to be the ultimate arbiter in Islamic affairs is primarily successful, though it is not without contestations. Due to the constricting nature of the political system, Muslim actors have largely tried to maximise their influence within the confines of what the state deems permissible either by not confronting the state directly or by overtly cooperating with it in some instances. Dissent towards the state-sanctioned version of Islam may arise in pockets, especially on social media, but it is limited both in scope and participation.